2009
DOI: 10.1103/physrevb.79.024110
|View full text |Cite
|
Sign up to set email alerts
|

Cooperativity among defect sites inAO2+xandA4O9

Abstract: Actinide dioxides derived from the AO 2 fluorite lattice are of high technological relevance due to their application in nuclear reactor fuels. In this paper we use density functional theory calculations to study the oxidation of uranium, neptunium and plutonium dioxides, AO 2 ͑A = U, Np, or Pu͒, in O 2 and O 2 / H 2 O environments. We pay particular attention to the formation of oxygen clusters ͑cooperativity͒ in AO 2+x and how this phenomenon governs oxidation thermodynamics and the development of ordered A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
103
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(117 citation statements)
references
References 55 publications
(89 reference statements)
14
103
0
Order By: Relevance
“…Since the GGA+U and LDA+U give the similar description of the PDOS, here we only plot the GGA+U results. The orbital-resolved PDOS of the bulk PuO 2 at the ground state has been calculated and analyzed in detail by previous DFT+U [19,21,22,24] and hybrid DFT [9,16] studies, and those theoretical results of DOS are usually tested by comparing with the experimental photoelectron spectroscopy (PES) measurements [6,7].…”
Section: Resultsmentioning
confidence: 99%
“…Since the GGA+U and LDA+U give the similar description of the PDOS, here we only plot the GGA+U results. The orbital-resolved PDOS of the bulk PuO 2 at the ground state has been calculated and analyzed in detail by previous DFT+U [19,21,22,24] and hybrid DFT [9,16] studies, and those theoretical results of DOS are usually tested by comparing with the experimental photoelectron spectroscopy (PES) measurements [6,7].…”
Section: Resultsmentioning
confidence: 99%
“…Previous papers considered mechanisms of xenon transfer and its interaction with uranium in UO 2+x (ref 9) theoretically, as well as the influence of defects 10,11 and pressure 12, 13 on the ionic composition of these oxides. Adsorption energies of water on differently oriented uranium dioxide planes were calculated.…”
Section: Introductionmentioning
confidence: 99%
“…The effective modification of pure DFT by LDA/GGA+U formalisms has been confirmed widely in studies of PuO 2 [27][28][29][30][31][32][33][34][35], which have reported the AFM-insulator ground state of…”
Section: Introductionmentioning
confidence: 98%